Clinical study of Jianpi Qingchang decoction in the treatment of ulcerative colitis patients with spleen deficiency and dampness-heat syndrome accompanied by fatigue: Study protocol for a randomized controlled trial - Liu, Zi-Xuan; Liu, Xiao-Yan; Tan, Wei-wei; Zhang, Wei-Bing; Zhang, Ya-Li; Zheng, Lie; Dai, Yan-Cheng (Contemporary clinical trials communications, 2024)
Ulcerative colitis (UC) is a chronic non-specific inflammatory intestinal disease, categoried under "dysentery" and "intestinal bleeding" in Traditional Chinese Medicine (TCM). Jianpi Qingchang decoction (JPQC) is a combination formula specifically designed for the treatment of UC. The primary objective of this study is to examine the clinical efficacy of JPQC in individuals diagnosed with UC who exhibit both spleen deficiency and dampness-heat syndrome, along with the presence of fatigue. The investigation will focus on assessing the impact of JPQC on the gut microbiota and metabolites in these patients, aiming to elucidate the regulatory mechanism that JPQC exerts on the gut microbiota and metabolites in the context of UC-related fatigue. In this randomized clinical trial, 140 subjects diagnosed with UC will be recruited and randomized into two groups. They will receive either JPQC combined with mesalazine or mesalazine alone for 12 weeks. Follow-up visits will be conducted every four weeks, with a post-treatment visit scheduled at 6 months. The primary outcome measures include the Inflammatory bowel disease fatigue scale(IBD-F). Secondary efficacy indicators comprise the assessment of TCM syndrome and individual syndrome efficacy before and after treatment, Modified Mayo score, Simple clinical colitis activity index (SCCAI), as well as the Inflammatory Bowel Disease Questionnaire (IBDQ) for each group. The other outcomes are the Intestinal microbial diversity and non-targeted metabonomics, which will be measured at baseline and 12 weeks after randomization. If effective, JPQC will provide substantial clinical evidence concerning the effectiveness and safety in the treatment of patients with UC experiencing spleen deficiency and dampness-heat syndrome accompanied by fatigue. ChiCTR2300068348.